2010
DOI: 10.1007/s13353-010-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

HMG1A and PPARG are differently expressed in the liver of fat and lean broilers

Abstract: The expression of nine functional candidates for QT abdominal fat weight and relative abdominal fat content was investigated by real-time polymerase chain reaction (PCR) in the liver, adipose tissue, colon, muscle, pituitary gland and brain of broilers. The high mobility group AT-hook 1 (HMG1A) gene was up-regulated in liver with a ratio of means of 2.90 (P ≤ 0.01) in the «fatty» group (relative abdominal fat content 3.5 ± 0.18%, abdominal fat weight 35.4 ± 6.09 g) relative to the «lean» group (relative abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
(24 reference statements)
1
16
0
3
Order By: Relevance
“…This reflects altered nutrient partitioning in high feed efficiency birds which is likely multifaceted, involving changes to metabolic processes in several organs such as reduced adipogenesis in abdominal fat, reduced lipogenesis in the liver, and increased lipoprotein triglyceride hydrolysis in skeletal muscle. Regardless of the specific biological mechanisms, there is evidence that improvements to such performance traits are associated with a shifting of fat metabolism away from the liver and normal adipose depots toward skeletal muscle (Griffin et al, 1989;Larkina et al, 2010;Zhuo et al, 2015). In commercial broiler chickens, selection for large breast muscle partitions more nutrients toward the pectoralis major, which may be particularly susceptible to metabolic perturbations due to its primary composition of type IIB glycolytic muscle fibers (Anderson and Neufer, 2006).…”
Section: Broiler Selection and Wooden Breastmentioning
confidence: 99%
“…This reflects altered nutrient partitioning in high feed efficiency birds which is likely multifaceted, involving changes to metabolic processes in several organs such as reduced adipogenesis in abdominal fat, reduced lipogenesis in the liver, and increased lipoprotein triglyceride hydrolysis in skeletal muscle. Regardless of the specific biological mechanisms, there is evidence that improvements to such performance traits are associated with a shifting of fat metabolism away from the liver and normal adipose depots toward skeletal muscle (Griffin et al, 1989;Larkina et al, 2010;Zhuo et al, 2015). In commercial broiler chickens, selection for large breast muscle partitions more nutrients toward the pectoralis major, which may be particularly susceptible to metabolic perturbations due to its primary composition of type IIB glycolytic muscle fibers (Anderson and Neufer, 2006).…”
Section: Broiler Selection and Wooden Breastmentioning
confidence: 99%
“…Previous analysis showed that PPARG expression is more than 3-fold upregulated in "fat"chickens. The primer pairs used in that analysis, however, measured the expression of all gene transcripts (Larkina et al, 2011). The design of transcript specific primers allowed us to measure the expression of each transcript reported for the PPARG gene (GeneID:373928).…”
Section: Discussionmentioning
confidence: 99%
“…Transcript-specific primers were designed using data information from the chicken genome assembly Gallus_gallus-5.0 (GenBank Acc NC_006099.4) using the software PRIMER 3 http://bioinfo.ut.ee/ primer3-0.4.0 (Koressaar & Remm, 2007;Untergasser et al, 2012). The primer sequences are presented in Table 2.GAPDH was used as reference gene as in our previous experiments (Larkina et al, 2011). We applied the following primers for GAPDH expression profiling: GAPDHfw, CCTCTCTGGCAAAGTCCAAG and GAPDHrv, CATCTGCCCATTTGATGTTG.…”
Section: Primer Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In fatty broiler chickens, cPPAR γ mRNA expression is induced in liver but not in adipose [16]. Because PPAR γ mRNA is induced in adipose tissue of obese mammals [17, 18], the result indicates a divergence of PPAR signal transduction mechanisms between avians and mammals.…”
Section: Regulators Of Cppar Mrnasmentioning
confidence: 99%